Language means used to show respect in Uzbeki and English - Qodirova , Marg‘uba (The Lingua Spectrum, 2025)
Respective devices are found at different levels of the language. Also, the meaning of respect can be expressed from the syntactic and stylistic point of view. In the process of analyzing the text, in addition to many morphological and grammatical tools available in the Uzbek language, word combinations, simple and complex sentence structures - phraseological tools, folk wisdom are widely used to express respect in speech. The category of respect clearly shows the relevance of the national mentality. This article aims to analyze the means used to express politeness in Uzbek and English languages. The article explores the cultural and social characteristics of both languages, as well as their literary and formal forms. Additionally, it highlights the role of language in conveying respect and its significance in the field of linguistics.